Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2015)
In this issue, there are three concepts that stand out as particularly important: Equality, Trust, and Agency. Three articles have equality as normative guideline. In the first article, it is analyzed how inequality is reproduced in recruitment practices, even when laws and formal rules are respected. A second article examines class and gender inequality, related to berth, maternity leave, work orientation, and the return to the labor market. A third article examines the evolution of government policy for gender equality. The concept of trust is analyzed theoretically in one article. Agency is highlighted in two articles. The analyses of the first article is at the micro level. Here, it is investigated how agency in daily work is challenged when municipalities are exposed to major reforms. Analyses in the second article are on the macro level. Here, it is investigated how European trade unions can influence EU policy (...)